Chromatin loop domain organization within the 4q35 locus in facioscapulohumeral dystrophy patients versus normal human myoblasts - Petrov, Andrei (National Academy of Sciences, 2006)
Fascioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant neuromuscular disorder linked to partial deletion of integral numbers of a 3.3 kb polymorphic repeat, D4Z4, within the subtelomeric region of chromosome 4q. Although the relationship between deletions of D4Z4 and FSHD is well established, how this triggers the disease remains unclear. We have mapped the DNA loop domain containing the D4Z4 repeat cluster in human primary myoblasts and in murine–human hybrids. A nuclear matrix attachment site was found located in the vicinity of the repeat. Prominent in normal human myoblasts and nonmuscular human cells, this site is much weaker in muscle cells derived from FSHD patients, suggesting that the D4Z4 repeat array and upstream genes reside in two loops in nonmuscular cells and normal human myoblasts but in only one loop in FSHD myoblasts. We propose a model whereby the nuclear scaffold/matrix attached region regulates chromatin accessibility and expression of genes implicated in the genesis of FSHD.